Metallicity and Paramagnetism of Single‐Crystalline NiTe and NiTe2. Issue 1 (25th August 2019) - Mao, Qianhui; Zhang, Yannan; Chen, Qin; Li, Ruixue; Geng, Xiaodong; Yang, Jinfeng; Hao, Haoshan; Fang, Minghu
Abstract : The synthesis, electrical resistivity ρ ( T ), and magnetic susceptibility χ ( T ) of single‐crystalline NiTe and NiTe2 are reported. The two compounds display good metallic behavior with χ (300 K) ≈3.6 μΩ cm, and ρ ( T ) at low temperature can be well described by Fermi‐liquid theory. χ ( T ) measurements suggest that both samples exhibit Pauli‐like paramagnetism. The Pauli magnetic susceptibility of NiTe is strongly enhanced, implying it is in proximity to magnetic instability. Abstract : Bulk single‐crystalline NiTe and NiTe2 are synthesized by chemical vapor transport method and are characterized by X‐ray diffraction and energy‐dispersive X‐ray spectroscopy. The metallicity and Pauli paramagnetism of these samples are identified by electrical resistivity and magnetic susceptibility measurements. The Pauli magnetic susceptibility of NiTe is strongly enhanced compared with NiTe2 .